Simbol Dan Fungsi Atribut Kerbau Pada Perayaan Gumbrekan Mahesa - Putri Rashinta Damayanti; Indah Rahmadianti; Nanda Fatma Nuraini; Adelia Efriliana; Wachidatul Linda Yuhanna (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
One of the local traditions in Banyubiru Village is “Gumbrekan Mahesa” which is commemorated once a year. Gumbrekan Mahesa's local wisdom is believed to be a form of gratitude for the residents for the harvest gift given by God Almighty. The urgency of this research is the need to study local wisdom, especially the attributes used by the village community of Kampung Kerbau Banyubiru as basic data for the development of cultural tourism and creative economic potential in Ngawi Regency. In addition, it also provides an overview of the value of cultural wealth in today's society and young generation. The aims of this research is to know the type, philosophy, and function of buffalo attributes in Gumbrekan Mahesa tradition. This research method is exploratory research, namely social research that aims to explain the concepts or patterns used. The primary data used are interview data and buffalo attribute observation data. Data analysis was carried out by interactive model analysis. The results showed that the attributes used in the Gumbrekan Mahesa tradition consisted of “Klothak, Pecut, Alu, Lesung, and teak leaf caping. The meaning and function of Klothak is as a marker when the buffalo is being herded in the forest and a medium of communication between the herder and the buffalo. Alu and lesung have the meaning of a tool to process food with patience and responsibility. Alu and Lesung are also used when herders get lost in the forest and bulfaloes are lost. Pecut is a tool to regulate the buffalo to run according to the direction of the shepherd which means to obey the leadership and the rules. Teak leaf caps are used by buffalo herders to protect themselves from heat and rain. This caping is also believed to be able to ward off lightning.